2022
DOI: 10.1177/23971983221074749
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis in Asians: Are there racial differences?

Abstract: Systemic sclerosis is a multisystemic autoimmune disease characterized by vasculopathy and fibrosis. Racial factors exert a significant influence on the epidemiology, clinical manifestations, antibody profile, mortality and genetic factors in systemic sclerosis. In this review, we examined Asian systemic sclerosis cohorts reported in Asia and multi-racial cohort studies to evaluate the disease characteristics and outcomes of systemic sclerosis in Asians. Asian patients have distinct genetic susceptibility to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…However, other studies reported a higher proportion of lcSSc in their studies [38,41]. Recently, a study among Asian SSc patients found that Asian patients have a distinct genetic susceptibility to systemic sclerosis, earlier systemic sclerosis onset, more diffuse skin involvement, and a more severe clinical phenotype [42]. This dissimilarity of the results might be due to the geo-epidemiological differences in studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, other studies reported a higher proportion of lcSSc in their studies [38,41]. Recently, a study among Asian SSc patients found that Asian patients have a distinct genetic susceptibility to systemic sclerosis, earlier systemic sclerosis onset, more diffuse skin involvement, and a more severe clinical phenotype [42]. This dissimilarity of the results might be due to the geo-epidemiological differences in studies.…”
Section: Discussionmentioning
confidence: 89%
“…A study conducted in Italy found that 100% had antinuclear antibodies, 37.5% had anti-topoisomerase antibodies, and 37.5% had anticentromere antibodies [41]. On the other hand, an Asian study documented 85.5% antinuclear antibody and 22.7% anticentromere antibody-positive patients [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the low frequency or low titres of these antibodies [ 26–28 ], which might prevent their detection by immunodot. It could be also attributed to other ethnic and environmental factors, even in the same Caucasian ethnicity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients of African descendance experience a higher incidence of the disease, earlier onset, more end-organ disease, lower quality of life, and higher mortality than White patients (8,11). Compared to White patients, Asian patients have a high prevalence of anti-topoisomerase I, anti-U1 RNP antibodies, interstitial lung disease, an earlier disease onset, and develop a scleroderma renal crisis less commonly (12). Studies in Asia have also highlighted differences in disease severity across different regions, with the diffuse cutaneous subset being more prevalent in Thailand, China, and India (13,14), in contrast with what is observed in Japan, Korea, and Iran (15,16).…”
Section: Introductionmentioning
confidence: 99%